The impact of entrepreneurial orientation on the supply chain resilience - Mohammed A. Al-Hakimi; Deleep B. Borade (Cogent Business & Management, 2020)
Despite the great interest that the concept of Supply Chain Resilience (SCR) has received over the past few years, empirical research examining its antecedents still limited, especially, in the context of small and medium enterprises (SMEs) in developing countries, like Yemen. Based on the resource-based view (RBV) and dynamic capabilities theory (DCT), this paper examines the impact of entrepreneurial orientation (EO) on SCR. Based on a research framework, a self-administered questionnaire was used to collect data from a sample consisted of 217 SMEs owners/or managers. A structural equation model was used to test the relationships in the proposed model. The results obtained appear that EO has a positive and significant effect on SCR of SMEs through its dimensions represented by innovativeness, risk-taking, and proactiveness, as opposed to autonomy that demonstrated a negative impact on SCR, while the effect of competitive aggressiveness was insignificant. These findings provide advantageous insights for SMEs, especially in the Yemeni manufacturing sector, which pursuing to be resilient towards any disturbance that may lead to disruption in their supply chains by adopting EO.
Keywords: 650; supply chain resilience; entrepreneurial orientation; resource based view; dynamic capabilities theory; SMEs